Estimation of permeability tensor and dielectric permittivity of ferrites using a wave guide method under a dc magnetic field - Tsiachristos, I.; Varouti, E.; Manios, E.; Stamopoulos, D.; Zervos, T.; Fikioris, G.; Lazarakis, F.; Alexandridis, A.; Pissas, M. (JEMS 2013 - JOINT EUROPEAN MAGNETIC SYMPOSIA, 2014)
Using a vector network analyzer equipped with a calibrated rectangular wave guide the electric permittivity and the element of the magnetic permeability tensor for Y3Fe5O12, ZnFe2O4 and NiFe2O4 are measured. The electric permittivity can be estimated from the body resonances (d = n lambda/2) if a sufficient long sample is used. The estimation of the magnetic permeability tensors' parameters can be estimated comparing the experimental results with computer simulations using the magnetic properties of the materials as derived from the magnetic measurements.